O projecto de pontes para vidas superiores a 100 anos - Branco, F.; Paulo, P. V. (Revista ALCONPAT, 2012)
A new philosophy for bridge design is presented for structures with more than 100 years of service life. It considers in an integrated way the design phase with special structural analysis and a durability study, the construction phase with high quality control and the service phase with monitoring and inspection within a management system. This methodology is illustrated with de design of the Vasco da Gama bridge which was the first Portuguese bridge to be designed for 120 years service life. Keywords: bridges; service life; durability; design; management.